Tablets containing açaí (Euterpe spp.) dried extract for dietary supplementation: A study of functional properties - ARELLANO, Lenin Fernández; DA COSTA, Russany SILVA; CONCEIÇÃO, Edemilson Cardoso da; RIBEIRO-COSTA, Roseane Maria; SILVA JUNIOR, José Otávio Carrera (Food Science and Technology, 2024)
Açaí is a very popular functional food in the Amazon due to its nutritional properties, its high caloric value, and its high content of anthocyanins and phenolic compounds, which mainly confers antioxidant and anti-inflammatory activities. Thus, this study aimed at the development of immediate-release tablets containing açaí dried extract by direct compression. The extract was subjected to physical evaluation of the powder, quantification of total polyphenol (TP) content (mg EAG/g), total anthocyanin content (mg C3G/100 g), cyanidin-3-rutinoside marker (µg C3R/g) by LC-MS, obtention of the tablet, and their physical-mechanical evaluation. Açaí dried extract showed spherical shape particles, with smooth and rough surfaces and heterogeneous sizes, which are characteristic of dried powders when obtained by spray drying. In addition, the extract presented TP content (23.307± 2.190 mg EAG/g), total anthocyanins (10.52 mg C3G/100 g), and cyanidin-3-rutinoside (42 µg C3R/g). Tablets had good mechanical properties, good thermal stability under 200°C, and 3.65 µg C3R/g of cyanidin-3-rutinoside content per tablet unit. The results obtained in this study showed the possibility of obtaining tablets containing açaí dried extract with good mechanical properties and antioxidant activity aiming its use as a dietary supplement.